2020
DOI: 10.1039/d0ra01239d
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a dual-phase CsPbBr3–CsPb2Br5 single crystal and its photoelectric performance

Abstract: Dual-phase CsPbBr3–CsPb2Br5 single crystal microsheets were synthesized by a simple method based on the coffee ring effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Such assembled materials are bound to contribute to the extra structure stability by strong interactions between the abundantly shared active atoms. 44 (3) As reported, by tuning the bromine chemical constitution and quantum confinement size to tailor the redox potential levels, CO 2 conversion may give an ideal selective product. 48,49 Remarkably, the constitution of bromine in the composite is easily controlled by monitoring the composition ratio of CsPbBr 3 and CsPb 2 Br 5 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Such assembled materials are bound to contribute to the extra structure stability by strong interactions between the abundantly shared active atoms. 44 (3) As reported, by tuning the bromine chemical constitution and quantum confinement size to tailor the redox potential levels, CO 2 conversion may give an ideal selective product. 48,49 Remarkably, the constitution of bromine in the composite is easily controlled by monitoring the composition ratio of CsPbBr 3 and CsPb 2 Br 5 .…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that in the presence of excess PbBr 2 , CsPbBr 3 could rearrange to form CsPb 2 Br 5 with a nonstoichiometric material transformation. , Thus, the consubstantial CsPbBr 3 QDs and CsPb 2 Br 5 nanosheets are expected to be synthesized in situ using a simple one-step hot-injection method with PbBr 2 as a scissor. Such assembled materials are bound to contribute to the extra structure stability by strong interactions between the abundantly shared active atoms . (3) As reported, by tuning the bromine chemical constitution and quantum confinement size to tailor the redox potential levels, CO 2 conversion may give an ideal selective product. , Remarkably, the constitution of bromine in the composite is easily controlled by monitoring the composition ratio of CsPbBr 3 and CsPb 2 Br 5 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Halide perovskites, possessing flexible lattices and exceptional optoelectronic properties, have achieved remarkable performance in the applications of solar cells, photodetectors, and light-emitting diodes (LEDs) but still suffer from problems, like the instability of ionic lattices. Two-dimensional (2D) inorganic CsPb 2 X 5 , as a derivative of CsPbX 3 perovskite, has attracted increasing attention owing to its unique optical properties and quantum confinement effects. They exhibit higher stability against moisture in an air environment, which benefits from the intrinsic structure with a layered arrangement of Pb–X polyhedron and Cs + . Research of the fundamental structure–property correlation of CsPb 2 X 5 could bring out the design inspiration of novel materials.…”
mentioning
confidence: 99%